PENYELESAIAN MODEL TRANSPORTASI MENGGUNAKAN METODE ASM - Nurul Iftitah; Pardi Affandi; Akhmad Yusuf (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2020)
Transportation problem is related by goods shipments from sources (supplies) to destination(demand). the method that could be used for solving the transportation problem is to directly find theoptimal solution. The direct method that used in this study id the ASM method for solving the balancetransportation problem and revised ASM method for solving the unbalance transportation problem.This study aims to construct a transportation model using those methods and it solution. The methodon this study is to identify the transportation model, construct the transportation model matrixes,construct an algorithm table using ASM method and to determine the optimal solution of thetransportation problem. The obtained result from this study was the model ASM method coulddetermine the optimum value without using initial feasible solution. On solving the unbalancetransportation problem, there is an addition of dummy cell or column step. Then reducing the cost ofcell and column and change the dummy cost with the biggest cost of reduced cell or column.